Using the Reproductive Life Plan in contraceptive counselling. (1st October 2016) - Tydén, Tanja; Verbiest, Sarah; Van Achterberg, Theo; Larsson, Margareta; Stern, Jenny
Abstract: Having children or not is one of the most important decisions that a person will make in his or her lifetime. The Reproductive Life Plan (RLP) is a protocol that aims to encourage both women and men to reflect on their reproductive intentions and to find strategies for successful family planning, for example to have the wanted number of children and to avoid unwanted pregnancies as well as ill-health that may threaten reproduction. The RLP was developed in an American context for promotion of reproductive health in a life cycle perspective. Few studies have systematically evaluated the effectiveness of using an RLP protocol in clinical practice. This article describes the application of using the RLP protocol in contraceptive counselling in Sweden.